2016
DOI: 10.1148/radiol.2015141507
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Automated Attenuation-based Tube Voltage Selection on Radiation Dose at CT: An Observational Study on a Global Scale

Abstract: ATVS significantly reduces radiation dose across most, but not all, body regions and types of CT examinations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 32 publications
1
31
1
Order By: Relevance
“…These results are in contrast to a study by Spearman et al [ 29 ], who evaluated the effect of ATVS on CT radiation dose, including all body regions and types of CT examinations in 164,323 unique CTs from all across the world. They observed, in non-enhanced chest CTs, a non-significant decrease in CTDI vol of -2.2%, but a significant decrease for enhanced chest CT of -14.3% [ 29 ]. In their study, however, they were not able to verify whether ATVS was consistently applied correctly with the appropriate settings [ 29 ].…”
Section: Discussioncontrasting
confidence: 91%
“…These results are in contrast to a study by Spearman et al [ 29 ], who evaluated the effect of ATVS on CT radiation dose, including all body regions and types of CT examinations in 164,323 unique CTs from all across the world. They observed, in non-enhanced chest CTs, a non-significant decrease in CTDI vol of -2.2%, but a significant decrease for enhanced chest CT of -14.3% [ 29 ]. In their study, however, they were not able to verify whether ATVS was consistently applied correctly with the appropriate settings [ 29 ].…”
Section: Discussioncontrasting
confidence: 91%
“…The patients were examined on the third-generation dual-source CT system (SOMATOM Force, Siemens Healthcare, Forchheim, Germany) [ 7 ] in dual-source, helical acquisition mode at a gantry rotation time of 0.25 s / rotation, pitch 1.9, 0.75 mm section thickness and 192 x 0.6 mm detector rows. In all examinations, automated attenuation-based tube voltage selection (CAREkV, Siemens Healthcare) [ 8 ] and tube current modulation along the z axis (CAREDose, Siemens Healthcare) was used with a quality reference tube voltage of 100 kV and a quality reference tube current time product of 220 mAs. The scan range covered the entire pulmonary parenchyma, extending from the costophrenic angle to the level of the pulmonary apex.…”
Section: Methodsmentioning
confidence: 99%
“…However, a previous global observational study showed various tube potentials selection (from 80 kVp to 140 kVp) for cerebral or carotid CTA (27).…”
Section: Discussionmentioning
confidence: 99%
“…The CT scanner used in a previous global study (27) had a maximum tube current capacity of 500 mA. For high radiation exposure setting or fast acquisition of CT images by using accelerated rotation time and high helical pitch, excess tube current capacity may be needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation